Marine Invasive Algae’s Bioactive Ingredients as a Sustainable Pathway in Cosmetics: The Azores Islands as a Case Study - Marta Matos; Luísa Custódio; Catarina Pinto Reis (Marine Drugs)
Marine invasive species pose significant ecological, economic, and social challenges, disrupting native ecosystems, outcompeting local species and altering biodiversity. The spread of these species is largely driven by global trade, shipping, and climate change, which allow non-native species to establish themselves in new environments. Current management strategies, including early detection, rapid response, and biosecurity measures, have had some success, but the complexity and scale of the problem require continuous monitoring. This review explores the possibility of using some marine invasive species as skincare ingredients and explores the Azorean islands as a case study for the valorization of biomass. Additionally, this review addresses legislative barriers that delay the development of sustainable cosmetic markets from invasive species, highlighting the regulatory landscape as a critical area. It concludes that marine invasive species present a regional and global problem that requires regional and global solutions. Such solutions strongly need to address environmental impacts and net socioeconomic benefits, but such solutions must also consider all regional differences, technical capacities and financial resources available. Thus, as a future perspective, strategies should emphasize the need for international collaboration and the development of more effective policies to prevent the spread of invasive species. There is still much work to be completed. By working together, the biodiversity for future generations will be better monitored and explored.